Bacterial Biofilms and Catheters: A Key to Understanding Bacterial Strategies in Catheter-Associated Urinary Tract Infection - J Curtis Nickel; J William Costerton (Canadian Journal of Infectious Diseases)
Despite major technological improvements in catheter drainage systems, the indwelling Foley catheter remains the most common cause of nosocomial infection in medical practice. By approaching this common complicated urinary tract infection from the perspective of the biofilm strategy bacteria appear to use to overcome obstacles to produce bacteriuria, one appreciates a new understanding of these infections. An adherent biofilm of bacteria in their secretory products ascends the luminal and external surface of the catheter and drainage system from a contaminated drainage spigot or urethral meatus into the bladder. If the intraluminal route of bacterial ascent is delayed by strict sterile closed drainage or addition of internal modifications to the system, the extraluminal or urethral route assumes greater importance in the development of bacteriuria, but takes significantly longer. Bacterial growth within these thick coherent biofilms confers a large measure of relative resistance to antibiotics even though the individual bacterium remains sensitive, thus accounting for the failure of antibiotic therapy. With disruption of the protective mucous layer of the bladder by mechanical irritation, the bacteria colonizing the catheter can adhere to the bladder’s mucosal surface and cause infection. An appreciation of the role of bacterial biofilms in these infections should suggest future directions for research that may ultimately reduce the risk of catheter-associated infection.